(untitled) (Scientific journal of the Fergana State University, 2024)
The article explores that varieties associated with the natural and climatic conditions of the Sokh region are the basis for the creation of semantic content, and the analysis of names associated with mountains, reservoirs, and residential areas increases the social significance of science. At the same time, the Sokh district has a peculiar national composition. Since ancient times, mainly Tajiks, partly Uzbeks and Kyrgyz, lived together in this territory. Of course, all these aspects influenced the formation of toponymic units. When studying the toponymy of a region based on linguistic characteristics, national, cultural, historical and political connections showed their influence, which is observed when naming other regions. The linguistic study of district toponyms contributes to the development of a number of other areas along with linguistics. Sokh district is one of the special socio-political and geographical regions of the Fergana region. For this reason, the study of toponymic units of this administrative region has a historical and ethnographic nature, taking into account the socio-political problems of our country and the fact that historical names have been preserved in large numbers. Sokh district is one of the densely populated places, but its administrative-territorial location has a complex structure, and it is an exclave of the Fergana region. It is also important and relevant to conduct a study of the toponymic units of the area.